Transatlantic civil society in periodicals, 1768-1925. - British Library (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2020)
This collection contains a series of American journals, magazines, and trade papers published in the United Kingdom and continental Europe from 1768 to 1925—a period that encompasses everything from the Boston Tea Party to the First World War. The periodicals are diverse in nature, but their focus is on social, cultural, and economic interchange between North America and Europe, with an emphasis on Anglo-American relations. Subject matter covered includes art (The Anglo-American Illustrated News), literature (The American Magazine), trade and commerce (The American Blue Book), leisure (American Referee And Cycle Trade Journal), tourism (The American Visitors’ News And Register And Colonial Gazette; America Abroad), émigré society gossip (American Society in Europe), politics (The London American), and white supremacy (The Anglo-Saxon), amongst other things.
Date range: 1768-1925.
Keywords: History, Modern -- Sources; World history -- Sources; North America -- History -- Sources; Europe -- History -- Sources